Antagonist Muscle Activation During Isometric Elbow Flexion at Varied Joint Angles: A Comparative Neuromuscular Analysis Between Volleyball Players and Sedentary Adults - Roy, Dipika; Pal, Manisha; Chatterjee, Priyam; Bandyopadhyay, Anupam (Stadium - Hungarian Journal of Sport Sciences, 2025)
Neuromuscular coordination enhances athletic performance and prevents injuries. Antagonist muscle activation during isometric movements, such as elbow flexion, is crucial for joint stability and efficiency. Volleyball-specific training may lead to distinct neuromuscular adaptations that differ from those of sedentary individuals. This study aims to investigate differences in antagonist activation patterns during isometric elbow flexion between volleyball players and sedentary adults, with a focus on neuromuscular control and the effects of co-contraction. Twenty-eight males (14 volleyball players and 14 sedentary individuals; ages 18–25) participated in the study. Surface electromyography (EMG) recorded biceps and triceps activity at 45°, 90°, and 120° elbow angles. Muscle activity, co-contraction indices (CCI), and perceived exertion (RPE) were statistically analyzed using descriptive statistics and two-way repeated measures Analysis of Variance. Bonferroni corrections assessed angle-specific effects. Significance levels (α) were set to 0.05 for all analyses. Athletes exhibited significantly higher biceps activation (mean EMGmax = 0.63 vs. 0.48) and lower triceps activation (mean EMGmax = 0.25 vs. 0.35, p < 0.001). Co-contraction (CCI) was lower among athletes (mean = 0.55 vs. 0.89). RPE scores were consistently lower in athletes (mean = 12.8 ± 1.6) compared to non-athletes (15.7 ± 1.5), indicating superior neuromuscular efficiency. Volleyball players demonstrated enhanced neuromuscular control, as evidenced by higher agonist activation, reduced antagonist activation, and lower co-contraction. The enhanced neuromuscular adaptations of volleyball players, likely resulting from consistent training, suggest improved movement mechanics and a reduced risk of injury. Future longitudinal studies are advised to explore causality and sport-specific neuromuscular changes.